The transmission of local wisdom in herbal processing of Pa Wa agroforestry network members, Kaeng Hang Maeo district, Chanthaburi province - Thongkaew, E.; Eamkijkarn, Sabaijai P.; Chatanan, P.; Kerdsriserm, C.; Khermkhan, J. (My University, 2025)
The content analysis revealed that the transmission of local wisdom in herbal processing among the agricultural network members involved in sender/source of information and transmitters, which included knowledgeable members of the network on herbal properties and processing methods, message or content are medicinal properties of herbs, processing procedures, and packaging methods, communication channels, including hands-on learning, demonstrations, practical involvement, and information exchange through discussions or inquiries, and the receivers of the transmitted knowledge, primarily network members, family members, relatives, and interested individuals participating in learning activities. The findings underscored the importance of preserving local wisdom in herbal processing within the community, as it resided within individuals and could potentially be lost. Therefore, it should focus on collecting and storing this knowledge for easier accessibility to ensure its continuity and potential development in the future.
Keywords: Herbal; Local wisdom; Transmission